2021
DOI: 10.1007/s11664-020-08597-7
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of 21H-SiC Thin Film-Based Schottky Barrier Diodes Using TiN Contacts

Abstract: The fabrication of Schottky barrier diodes based on thin films of 21H polytype of SiC is reported. The films were deposited using a single composite target of Si and graphite by magnetron sputtering. The formation of the 21H polytype of SiC was confirmed by x-ray diffraction. The devices were fabricated on single-crystal Si substrates, and electrical properties with TiN and Au/TiN as top lateral contacts were investigated. The rectifying nature, temperature (in the range 300-423 K), and top electrode work func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…This approach proposed by Werner and Güttler 13 and the apparent barrier height (Φ ap ) is always lower than the .…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…This approach proposed by Werner and Güttler 13 and the apparent barrier height (Φ ap ) is always lower than the .…”
Section: Resultsmentioning
confidence: 97%
“…In general, the BH value extracted from the standard TE theory is usually decrease with temperature and n increases due to the existence inhomogeneities of BH at M/S interface and these higher changes at lower temperaures cannot explain only in terms of standard TE and TFE theories. [11][12][13][14] The objective of this work is to an investigate temperature dependent basic electric parameters and possible CTCs in the Au/Al 2 O 3 /n-Si SDs between 200 K and 400 K by using the IV between ±3 V. In this study, the increase in BH observed with increase in the temperature, higher values of n even at room temperature, and the deviation linearity of the conventional RP were successfully explained by the GD-model.…”
mentioning
confidence: 81%
See 1 more Smart Citation